Pembuatan set eksperimen gerak harmonis sederhana pada bandul berbasis Sensor Ping dan Sensor Photogate dengan tampilan PC (Fabrication of a simple set of harmonic motion experiments on pendulum based on Ping Sensor and Photogate Sensor with PC display) - Lily Handayani; - Yulkifli; - Yohandri (PILLAR OF PHYSICS, 2019)
Physics experiments have a very important role. The most important thing that must be considered in conducting physics experiments is the set of experiments. One of the physics experiments that has been developed is the experimental set of simple harmonic motion in pendulum but not yet completely complete. The research that will be conducted is a type of R & D research with a 4D model. Where the 4D development model has 4 stages, define, design, develop and dissemination. The measurement technique used is direct and indirect measurements. Direct measurement is done to determine the angle used. Indirect measurements are made to determine the number of oscillations of pendulum (n), period (T), and length of rope (l). Data obtained through measurements in the form of data accuracy and accuracy and analyzed in two ways, namely statistically and graphically. So that the average accuracy is 98.60% and the average accuracy is 0.997 with a validity level of 86.66%.